Two By Two - Sparks, Nicholas; Fliakos, Ari (New York, NY : Hachette Audio, 2016)
At 32, Russell Green has it all: a stunning wife, a lovable six- year-old daughter, a successful career as an advertising executive, and an expansive home in Charlotte. But underneath the shiny surface of this perfect existence, fault lines are beginning to appear. In a matter of months, Russ finds himself without a job or wife, caring for his young daughter while struggling to adapt to a new and baffling reality. Throwing himself into the wilderness of single parenting, Russ embarks on a journey at once terrifying and rewarding--one that will test his abilities and his emotional resources beyond anything he ever imagined.
Keywords: Single fathers -- Fiction; Fathers and daughters -- Fiction; Man-woman relationships -- Fiction; Families -- Fiction; Charlotte (N.C.) -- Fiction; North Carolina -- Fiction; Audiobooks; Romance fiction